1994
DOI: 10.1007/bf00971576
|View full text |Cite
|
Sign up to set email alerts
|

Studies on lipid peroxidation in the rat brain

Abstract: The aim of this study was to set up a simple procedure for assessing lipid peroxidation (L.P.) and testing the activity of antioxidant compounds. L.P. was determined in rat brain homogenates by measuring the endogenous and stimulated accumulation of malonaldehyde (MDA). MDA was assayed by an HPLC method. Homogenates spontaneously formed appreciable amounts of MDA. The addition of increasing concentrations of FeCl2 resulted in a linear accumulation of MDA, up to 16.6-fold at 50 microM. An organic form of iron (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
71
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(75 citation statements)
references
References 35 publications
4
71
0
Order By: Relevance
“…MDA is a major reactive aldehyde that is formed during the final stages of lipid peroxidation of biological membrane polyunsaturated fatty acid (Cini et al, 1994). Our results demonstrated that the administration of H 2 O 2 caused an increase in the MDA concentration of the human dermal fibroblasts, while the application of Oatp decreased the MDA level, suggesting that Oatp was effective in scavenging free radicals and suppressing the production of MDA.…”
Section: Oatp Intervention In H 2 O 2 -Induced Fibroblast Damage Withmentioning
confidence: 53%
See 1 more Smart Citation
“…MDA is a major reactive aldehyde that is formed during the final stages of lipid peroxidation of biological membrane polyunsaturated fatty acid (Cini et al, 1994). Our results demonstrated that the administration of H 2 O 2 caused an increase in the MDA concentration of the human dermal fibroblasts, while the application of Oatp decreased the MDA level, suggesting that Oatp was effective in scavenging free radicals and suppressing the production of MDA.…”
Section: Oatp Intervention In H 2 O 2 -Induced Fibroblast Damage Withmentioning
confidence: 53%
“…MDA is a byproduct of lipid peroxidation and is widely used as a biomarker of oxidative stress (Cini et al, 1994). However, antioxidant enzymes, such as SOD and glutathione (GSH)-Px, are considered to effectively augment cells' antioxidant defenses (Luo and Xia, 2006).…”
Section: Oatp Intervention In H 2 O 2 -Induced Fibroblast Damage Withmentioning
confidence: 99%
“…When the ascorbate system was used, liver microsomes were heat-inactivated before the addition of the incubation mixture. Brain microsomal LP was determined according to Cini et al, 1994, using microsomes instead of brain homogenates. Microsomes were incubated at 37°C for 60 min without (spontaneous) and with the addition of a free-radical generator system (100 µM FeCl 2 ).…”
Section: Assay Of Lp In Liver and Brain Microsomesmentioning
confidence: 99%
“…MDA is a by-product of lipid peroxidation induced by excessive ROS and is widely used as a biomarker of oxidative stress [24] . Antioxidant enzymes, such as SOD and GSH-Px, however, are thought to be effective for the augmentation of antioxidant defenses in endothelial cells [25] .…”
Section: Discussionmentioning
confidence: 99%